Who Should be Taking Care of Children's Eyes? - Michaud, Langis; Mercier, Marie-Eve; Deschamps, Marie-Josee (Canadian Journal of Optometry, 2021)
The purpose of this study was to survey a population in the Montreal area (Quebec, Canada) for its opinion concerning the importance of making children's first eye examinations legally mandatory before the children start school.